2006
DOI: 10.1074/jbc.m604915200
|View full text |Cite
|
Sign up to set email alerts
|

Raising the Active Site of Factor VIIa above the Membrane Surface Reduces Its Procoagulant Activity but Not Factor VII Autoactivation

Abstract: Tissue factor, the physiologic trigger of blood clotting, is the membrane-anchored protein cofactor for the plasma serine protease, factor VIIa. Tissue factor is hypothesized to position and align the active site of factor VIIa relative to the membrane surface for optimum proteolytic attack on the scissile bonds of membrane-bound protein substrates such as factor X. We tested this hypothesis by raising the factor VIIa binding site above the membrane surface by creating chimeras containing the tissue factor ect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…When sTF bound to FVIIa it significantly restricted FVIIa’s motions, resulting in a fairly rigid sTF:FVIIa complex positioned almost perpendicular to the membrane surface [23], in excellent agreement with our previously published fluorescence resonance energy transfer studies [2426]. Positioning the active site of FVIIa site relative to the membrane may be important in aligning it with membrane-bound substrates (FIX and FX), and in fact we recently showed that perturbing this alignment compromises the ability of TF:FVIIa to activate FX [27]. …”
Section: Computational Studies Of Protein-membrane Interactions In Thsupporting
confidence: 82%
“…When sTF bound to FVIIa it significantly restricted FVIIa’s motions, resulting in a fairly rigid sTF:FVIIa complex positioned almost perpendicular to the membrane surface [23], in excellent agreement with our previously published fluorescence resonance energy transfer studies [2426]. Positioning the active site of FVIIa site relative to the membrane may be important in aligning it with membrane-bound substrates (FIX and FX), and in fact we recently showed that perturbing this alignment compromises the ability of TF:FVIIa to activate FX [27]. …”
Section: Computational Studies Of Protein-membrane Interactions In Thsupporting
confidence: 82%
“…In a similar way, it has been shown that when factor VIIa is captured by tissue factor on the cell surface, the distance of factor VIIa from the cell membrane is critical for the efficient activation of factor X. 36 In pro-uPA, two covalent connections exist between the protease domain and the linker/ATF, that is, the cysteine bridge and the amino acid backbone. In uPA, only one connection exists from the protease domain to the linker/ATF, that is, the cysteine bridge connection.…”
Section: Discussionmentioning
confidence: 96%
“…Initial rates of FVIIa-catalyzed hydrolysis of Chromozym t-PA substrate (Roche Applied Science, Indianapolis, Indiana, USA) were quantified as described [11]. Reaction conditions were: 5 nM FVIIa, 100 nM membTF, 1 mM Chromozym t-PA in HBSAC (25 mM HEPES pH 7.4, 100 mM NaCl, 5 mM CaCl 2 , 0.1% BSA, 0.1% NaN 3 ) with 0.1% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
“…Binding of FVIIa to membrane-anchored TF has multiple effects on enzyme activity: (a) TF allosterically activates FVIIa, independent of the membrane [2]; (b) TF is thought to contribute a substrate-binding site (exosite) to help recognize FIX and FX [3][6]; (c) phosphatidylserine (PS) dramatically increases rates of FIX and FX activation by TF/FVIIa [7]; and (d) TF fixes FVIIa’s active site at a set distance above the membrane surface, which may be important for optimal engagement of the scissile bonds of FIX and FX [8][11].…”
Section: Introductionmentioning
confidence: 99%